Another brick in the wall - Jensen, Embla (My University, 2021)
We must reduce our carbon emissions in order for future generations to have a decent life on earth. The construction sector accounts for a large part of the emissions and the buildings built today have a short life expectancy. To build is costly, both in terms of effort, money and climate impact. Therefore, it is important to use our resources as qualitatively and long-term as possible. This thesis seeks one approach for a sustainable way of building new buildings, with the focus on residential brick architecture. Brick is a material that ages well and in many cases brick architecture lasts longer than buildings built in other materials. Today, brick is used a lot in residential architecture in Sweden, but mainly as cladding, to cover concrete elements or a light structure. The brick only affects the design of the buildings in a superficial way, the detail solutions are not particularly cared for and the possibilities of brick are seldom explored. The aim of this thesis is to explore and show how masonry could be used in robust heavyweight construction showcasing the inherent materiality and characteristics of brick. The site chosen in Gamlestaden is a historic setting, surrounded by industrial brick architecture, that has proven to last longer than their initial program. This thesis also explores how to add a new building in an existing urban setting, that can act as a bridge between the old and the new as well as adding value for the people already living there. The method chosen is “Research by Design”. This means that design iterations in different mediums: sketches, models and pictures etc. is the main tool of investigation. The result is a detailed proposal of a large residential block in brick in Gamlestaden, Gothenburg.
Keywords: Brick, masonry, Gothenburg, residential architecture